The contribution of physical education and sports teachers in alleviating manifestations of introversion and isolation among middle school students - ben nadjema, noureddine (sports creativity, 2025)
The research summary focuses on the guidance services provided by physical education and sports teachers to alleviate introversion and isolation among middle school students. Teachers are the closest link to the student, and physical activity and sports provide a fertile environment for play, allowing students to express their normal or disturbed behavior, problems, and conflicts that they cannot express in other settings. Teachers can observe student behavior, social interaction with classmates during physical education and sports classes, interaction with play equipment, and various student reactions and accompanying emotions. They can also observe how students express their desires, needs, fears, and problems, especially in cases of excessive repetition, and identify deviant behavior patterns such as isolation and introversion. From this perspective, the researcher, through theoretical and applied studies, aimed to examine and measure the extent to which physical education and sports teachers utilize the play environment to identify and diagnose manifestations of introversion and isolation among students, and the degree to which they contribute to mitigating these manifestations. To this end, the researcher prepared a questionnaire administered to a sample of Physical education and sports teachers at the middle school level, and the results of this survey showed that most physical education and sports teachers do not contribute sufficiently to alleviating the manifestations of introversion and isolation among middle school students.